The Influence of Profitability, Liquidity and Tax Avoidance on Firm Value (Case Study in Stock Exchange Mining Sector Companies Indonesia Period 2019 - 2021) - Latersia Br Gurusinga; Natasya Lovett Michelle (International Journal of Economics (IJEC), 2023)
This study aims to examine and analyze the effect of Profitability, Liquidity, and Tax Avoidance on the Company Value of Mining Sector Companies listed on the Indonesia Stock Exchange in 2019-2021. The research methodology used is a quantitative descriptive method. In this study, the population used is all mining listed on the Indonesia Stock Exchange from 2019 to 2021 with a total of 28 companies. Sampling Using the purposive sampling method, namely the technique of determining the sample with certain considerations and obtaining as many as 72 research samples from 24 companies. The results of the research analysis shexamines and analysesow that profitability has a tcount (3.003) > ttable (1.995) with a significant level of 0.004 <0.05 so it can be concluded that profitability has a positive and significant effect on firm value. Liquidity has a value of -tcount (-2.023) < -ttable (1.995) with a significant level of 0.047 <0.05 so it can be concluded that Liquidity has a negative and significant effect on Firm Value. Tax Avoidance has a value of -tcount (-0.327) > -ttable (-1.995) with a significant level of 0.745 > 0.05 so that it can be concluded that Tax Avoidance has a negative and not significant effect on firm Value. Profitability, Liquidity, and Tax Avoidance have a value of Fcount (4.435) < Ftable (3.13) with a significance of 0.007 > 0.05 so it can be concluded that simultaneously the variables Profitability, Liquidity and Tax Avoidance have a positive and significant effect on Firm Value.